(untitled) (Community Based Medical Journal, 2026)
Suicide by hanging is a major public health issue worldwide. A retrospective, cross-sectional study was conducted in the Department of Forensic Medicine & Toxicology, Sir Salimullah Medical College, Dhaka, Bangladesh, between February 2024 and January 2025, to examine the demographic patterns, circumstantial factors, and postmortem findings of suicidal hanging cases. A total of 155 cases of suicidal hanging were purposively selected based on autopsy reports, medical records, and police inquest documents. Our data revealed a male predominance (70.3%) and the most vulnerable age group was 20-30 years (45.2%). Most victims were unmarried (58.1%), unemployed (32.9%), or daily wage laborers (25.8%). Night-time incidents (42.6%) was predominent, while most used tools was rope (63.2%). Autopsy findings showed oblique ligature marks (76.8%), thyroid fractures (64.5%), petechiae (52.3%), and tongue protrusion (38.7%) as establishing characteristic patterns in suicidal hanging. This forensic analysis identified that young, unmarried males as the highest-risk demographic for suicidal hanging in Bangladesh, along with low socioeconomic factor being one of the key determinants. The findings underscore the urgent need for targeted prevention strategies and improved mental health support for vulnerable populations. CBMJ 2026 January: vol. 15 no. 01 P:61-66